Distribution and abundance of cassava pests in Tanzania with a note on the spiralling whitefly - Gnanvossou, D.; Hanna, R.; Pallangyo, B.; Toko, M.; Nsami, E.; Mfugale, O. (International Society for Tropical Root Crops, 2007)
Two surveys were conducted in Tanzania in May- June 2003 and June-August 2004 to determine the incidence and severity of several cassava arthropod pests including cassava green mite, cassava mealybug, spiralling whitefly, Bemisia spp., cassava scale, red mite, Zonocerus elegans, and several species of termites. Cassava green mite densities were relatively low except in the Lake region in 2004. The introduced phytoseiid predator of cassava green mite Typhlodromalus aripo was found in all regions, with the highest abundance in the Eastern and Lake regions in 2003, and in the Eastern region in 2004. Cassava mealybug infestations were very low throughout the surveyed regions, while B. tabaci (probably in mixed infestations with B. afer) were found in all regions but never exceeding 5 nymphs per leaf. Termite damage was widespread but impact on plant growth and yield is not known. Cassava scale was found only in few fields in the Southern Highlands, Lake and Eastern regions, with damage severity ranging from 2 to 4 (on a scale of 1 to 5). The spiralling whitefly Aleurodicus dispersus, first recorded in Zanzibar in 2002, was found for the first time on the mainland, but only in the Eastern region and at low infestation levels.